2nd paper Prize at the BMVA (British Machine Vision Association) PhD student paper competition - Lanitis, Andreas (My University, 2026)
2nd paper Prize at the BMVA (British Machine Vision Association) PhD student paper competition. The competition included the submission of an extended abstract and an oral presentation
Keywords: Education